Assessment of Surface Runoff for Tank Watershed in Tamil Nadu Using Hydrologic Modeling - Marykutty Abraham; Riya Ann Mathew (International Journal of Geophysics)
Providing safe and wholesome water in sufficient quantity on a sustainable basis remains elusive for large population especially in semiarid regions and hence water balance estimation is vital to assess water availability in a watershed. The water balance study is formulated to assess the runoff that can be harvested for effective utilization. The study area is Urapakkam watershed with a chain of 3 tanks having an aerial extent of 4.576 km2 with hard rock formation underneath and thus has limited scope for groundwater recharge. Hence surface water is the main water source in this area. Runoff computed for the watershed using USDA-NRCS model varied from 94.95 mm to 2324.34 mm and the corresponding rainfall varied from 575.7 mm to 3608.0 mm, respectively. A simple regression model was developed for the watershed to compute runoff from annual rainfall. Average annual runoff estimated for the watershed was around 37% of the rainfall for the study period from 2000-01 to 2013-14. Statistical analysis and test of significance for runoff obtained by NRCS model and regression model did not show any significant difference thus proving that regression model is efficient in runoff computation for ungauged basins. The volume of water accessible for fifty percent dependable flow year is obtained as 2.46 MCM and even if 50% of it can be effectively harnessed the water available in the watershed is 1.23 MCM. The water demand of the area is estimated as 0.148 MCM for domestic purpose and 0.171 MCM for irrigation purpose, which is much lower than the available runoff that can be harnessed from the watershed. Thus there is scope to harvest 1.23 MCM of water which is more than the demand of the watershed. The study reveals that it is feasible to harvest and manage water effectively if its availability and demand are computed accurately.